Essential-oil pesticidal odorscapes: An exploratory multi-endpoint framework for profiling plant volatiles against walnut-associated stored-product beetles - Gabriel Omar Denett; Maria Rosa Rodriguez; Virginia L. Usseglio; Daniela Milagros Bracamonte; Tamara Elizabeth López; Jose Francisco Aranda Cano; María Paula Zunino; Jorge Omar Werdin Gonzalez; Diego Alejandro Sampietro; Nieves Carolina Comelli (Journal of Stored Products Research, 2027)

Models based on urbanization and environmental heterogeneity jointly explain the distribution of plant species diversity and composition in urban green spaces - Armando Navarrete-Segueda; Jorge Cortés-Flores; Elizabeth Chávez-García; M. Lourdes González-Arqueros; Guadalupe Cornejo-Tenorio; Diana Santillán-Gaona; Abril Soria-Nambo; Iván Leonardo Ek-Rodriguez; Guillermo Ibarra-Manríquez (Urban Forestry & Urban Greening, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Rethinking nature-based solutions in informal settlements: community perceptions of urban risk in Durán, Ecuador - Margot Mattson; Isabella Pacenza; Shruti Jadala; Carlos Romero; Addison Martin; Marta Berbes-Blazquez; Elizabeth M. Cook; Mathieu Feagan; Mercy Borbor-Cordova; Pilar Cornejo-Rodriguez; Nancy B. Grimm (Climate and Development, 2026)

Governance Arrangements That Fit Social‐Ecological Context Are Associated With Fishery Sustainability - Mateja Nenadović; Alfredo Giron; Timothy Frawley; Adrian Munguia‐Vega; Kara E. Pellowe; Erica Ferrer; David Gill; Blanca González‐Mon; Andrew F. Johnson; Emilie Lindkvist; Fiorenza Micheli; Amy H. Weaver; et al. (Fish and Fisheries, 2026)
In many parts of the world, natural resources are primarily managed by governance arrangements at the local level. Those arrangements range from collective, such as cooperatives and associations, to individualistic, such as patrons and owner‐operators. A key question is how such arrangements influence resource use and associated social and ecological outcomes. We hypothesize that sustainable resource use is not associated with a specific governance arrangement, but instead that every type of arrangement has a certain set of social and ecological conditions under which sustainable resource use is feasible. This hypothesis was empirically investigated using fisheries landings data from Mexico. We found that sustainable resource use can be achieved through multiple governance arrangements provided that they are matched to appropriate social‐ecological contexts. Our findings help identify which governance arrangements are best suited to particular contexts and provide the initial building blocks for developing a theory of governance contextual fit in social‐ecological fishing systems.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Decent work in fishing in a changing climate - Michelle Tigchelaar; Bethany Jackson; Elizabeth R. Selig; Adrianna Davis; Emily O’Regan; Trond Kristiansen; Shinnosuke Nakayama; Doreen Boyd; William W.L. Cheung; Edgar Rodriguez-Huerta; Chris Williams; Jessica L. Decker Sparks (Marine Policy, 2025)

Evaluating Ecological Restoration Through Natural Regeneration Requires Replicated Landscape‐Scale Monitoring Studies - Michiel van Breugel; Maria Elizabeth Rodriguez‐Ronderos; Jefferson S. Hall; Daisy Dent; Dylan Craven (Global Change Biology, 2025)

Mechanisms and Therapeutic Potential of Key Anti-inflammatory Metabiotics: Trans-Vaccenic Acid, Indole-3-Lactic Acid, Thiamine, and Butyric Acid - Muñoz-Olivos Cristina; Bautista-Rodriguez Elizabeth; Rivas-Arreola María Jose; Palacios-Gonzalez Berenice; Zacapa Diego; Cortez-Sanchez Jose Luis (Probiotics and Antimicrobial Proteins, 2025)

Adventively established Leptopilina japonica: a new opportunity for augmentative biocontrol of Drosophila suzukii - Marco Valerio Rossi-Stacconi; Paul K. Abram; Gianfranco Anfora; Elizabeth Beers; Antonio Biondi; Nicolas Borowiec; Juli Carrillo; Jana Collatz; Asia Colmagro; Benjamin Crossman Johnson; Kent Daane; Giovanni Dal Zotto; et al. (Journal of Pest Science, 2025)
The invasive spotted-wing drosophila, Drosophila suzukii , has emerged as a significant global pest over the past decade, threatening fruit production worldwide. The parasitoid Leptopilina japonica , presumed native to East Asia, has established adventive populations in Europe and North America and is increasingly recognized for its ability to parasitize substantial proportions of D. suzukii larvae across diverse habitats. Here, we provide a broad review of the biology, establishment, distribution, and potential impacts of L. japonica . Using field data from international monitoring programs, we document the seasonal dynamics of plant–host–parasitoid associations and assess evidence for L. japonica ’s impact on D. suzukii and non-target organisms. Findings indicate that L. japonica has successfully established in several areas where D. suzukii is present in Europe and North America, showing promise as a biological control agent to support sustainable pest management. Current data suggest it provides some suppression of D. suzukii populations with minimal non-target effects. However, long-term studies are necessary to clarify its food web interactions and efficacy as a biological control agent. In areas where L. japonica has been established, we propose its use in augmentative biological control programs to enhance its impacts in specific agricultural settings. Case-specific evaluations of its ecological effects and role in integrated pest management, supported by continued monitoring, are essential. The case of L. japonica illustrates the need for clear, research-informed policies to guide the use of adventively established non-indigenous natural enemies in pest management.

Host‐Microbiome Associations in Livebearing Fishes Adapted to Toxic Environments Rich in Hydrogen Sulfide - Elizabeth J. Wilson; Sonny T. M. Lee; Lydia H. Zeglin; Lenin Arias Rodriguez; Michael Tobler (Molecular Ecology, 2025)
Organisms inhabiting extreme environments must tolerate a variety of physiochemical stressors. In some cases, host‐associated microbial communities facilitate the survival of their hosts in extreme environments, but extremophile symbioses have not been identified in vertebrates. We used 16S rRNA amplicon sequencing to investigate commonalities and differences in the gut bacterial communities of livebearing fishes ( Poecilia mexicana species complex, Poeciliidae) that have repeatedly colonised toxic sulfide streams in southern Mexico. We found shared gut microbial taxa across habitat types and drainages but also differences in the microbiomes between sulfidic and nonsulfidic populations, both in terms of patterns of diversity and community composition. Most importantly, we documented convergent changes in microbiome composition across evolutionarily independent sulfide spring lineages. These patterns were consistent when we analysed the gut microbiomes as well as primarily host‐associated microbiomes that excluded taxa that are commonly found in the environment. Our analyses also revealed several microbial taxa associated with sulfide spring coloniation that have previously been implicated in symbioses and may influence the host's tolerance to the extreme environmental conditions. Our study sheds light on how shared environmental pressures can give rise to convergent host‐microbiome associations in fishes, and it provides a foundation for investigating the role of host‐microbiome interactions in vertebrate adaptation to extreme environments.

Evaluating 3D-Printed Pre-separator Inserts in a Fast Screening Impactor for Physicochemical Characterization of Fine Particle Dose Release from Dry Powder Inhalers - Nathan A. Reed; Roee Dar; Nicholas Holtgrewe; Leo N. Y. Cao; Xiaofei Liu; Denise S. Conti; Bryan Newman; Elizabeth Bielski; Jason D. Rodriguez; Changning Guo (AAPS PharmSciTech, 2025)

Beyond the bite: how mosquito salivary proteins modulate midgut biology and malaria parasite transmission - Thiago Luiz Alves e Silva; Renuka Elizabeth Joseph; Joel Vega-Rodriguez (Current Opinion in Insect Science, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Vitamin C alleviates hyperglycemic stress in retinal pigment epithelial cells - Hamid Alahmari; Chia-Chun Liu; Elizabeth Rubin; Venice Y. Lin; Paul Rodriguez; Kun-Che Chang (Molecular Biology Reports, 2024)

Diving into the metabolic interactions of titanium dioxide nanoparticles in “Sparus aurata” and “Ruditapes philippinarum” - Mário Jorge Araújo; María Vazquez; Laura Rodriguez-Lorenzo; Antonio Moreda-Piñeiro; Elza Fonseca; Natalia Mallo; Ivone Pinheiro; Monica Quarato; Elizabeth Bigorra-Ferré; Ana Matos; Aldo Barreiro-Felpeto; Maria V. Turkina; et al. (Environmental Pollution, 2024)

Spatially heterogeneous discharge of glacial meltwater to drainages surrounding the ablating Coropuna ice cap, Peruvian Andes - Elizabeth J. Olson; Lisa R. Welp; Marty D. Frisbee; Sebastián A. Zúñiga Medina; Odiney Alvarez-Campos; Wendy R. Roque Quispe; Carol I. Salazar Mamani; Midhuar R. Arenas Carrión; José Diaz Rodriguez; Juan Manuel Jara Gonzalez; Alexander Ccanccapa-Cartagena; Chad T. Jafvert (Hydrological Sciences Journal, 2024)

Combined and sequential exposure to prenatal second hand smoke and postnatal maternal distress is associated with cingulo-opercular global efficiency and attention problems in school-age children - Paige B. Greenwood; Mariah DeSerisy; Emily Koe; Elizabeth Rodriguez; Leilani Salas; Frederica P. Perera; Julie Herbstman; David Pagliaccio; Amy E. Margolis (Neurotoxicology and Teratology, 2024)

Insights on the directional movement of Prunus necrotic ringspot virus between peach and wild Prunus species - Fabian Rodriguez Bonilla; Mandeep Tayal; Juan Carlos Melgar; Elizabeth Cieniewicz (Journal of Plant Pathology, 2023)

Unrecognized species diversity and endemism in the cichlid genus Bujurquina (Teleostei: Cichlidae) together with a molecular phylogeny document large-scale transformation of the western Amazonian river network and reveal complex paleogeography of the Ecuadorian Amazon - Oldřich Říčan; Štěpánka Říčanová; Luis Roger Rodriguez Haro; Cecilia Elizabeth Rodriguez Haro (Hydrobiologia, 2023)

Associations between trait food craving and adolescents’ preferences for and consumption of healthy versus unhealthy foods - Thomas P. Le; Ariana DeJesus-Rodriguez; Tripat K. Rihal; Elizabeth B. Raposa (Food Quality and Preference, 2023)

Supporting the Next Generation of Leaders in the Geosciences: Barnard’s Environmental Science Pathways Scholar Program - Logan Brenner; Brian Mailloux; Sedelia Rodriguez; Terryanne Maenza-Gmelch; Elizabeth Cook; Fatima Koli; Christine Marizzi; Rob Frawley; Batoul Saad; Martin Stute (Oceanography, 2023)
To address the national need to diversify the geosciences, we created the cohort-based Environmental Science Pathways Scholars Program, or E(SP)2, for undergraduates in the Environmental Science Department at Barnard College who identify as Black, Indigenous, and people of color (BIPOC), first generation, or low income. By fostering a more inclusive community in the particularly formative stages of academic and early professional development, E(SP)2 aims to support and retain a diverse cohort of students who have developed confidence in their scientific skills and identities, and who share a passion for environmental science. E(SP)2 is modeled on the Science Pathways Scholar Program [(SP)2] at Barnard College, an active and successful multidisciplinary opportunity at Barnard College.

Diagnosis of bacterial meningitis caused by Streptococcus pneumoniae, Neisseria meningitidis, and Haemophilus influenzae using a multiplex real-time PCR technique - María Noemí Carnalla-Barajas; Araceli Soto-Noguerón; Lucila Martínez-Medina; Maria Elizabeth Olvera-Herrera; Juan Luis Mosqueda-Gómez; Patricia Rodríguez-Cortez; Rayo Morfin-Otero; Eduardo Rodriguez-Noriega; Antonio Luévanos-Velázquez; Mariana Merlo-Palomera; Sergio Esparza-Ahumada; Francisco Márquez-Díaz; et al. (Brazilian Journal of Microbiology, 2022)

Enacting boundaries or building bridges? Language and engagement in food-energy-water systems science - Valoree S. Gagnon; Chelsea Schelly; William Lytle; Andrew Kliskey; Virginia H. Dale; Anna-Maria Marshall; Luis F. Rodriguez; Paula Williams; Michael Waasegiizhig Price; Elizabeth A. Redd; Margaret A. Noodin (Socio-Ecological Practice Research, 2022)
Scientific study of issues at the nexus of food–energy–water systems (FEWS) requires grappling with multifaceted, “wicked” problems. FEWS involve interactions occurring directly and indirectly across complex and overlapping spatial and temporal scales; they are also imbued with diverse and sometimes conflicting meanings for the human and more-than-human beings that live within them. In this paper, we consider the role of language in the dynamics of boundary work, recognizing that the language often used in stakeholder and community engagement intended to address FEWS science and decision-making constructs boundaries and limits diverse and inclusive participation. In contrast, some language systems provide opportunities to build bridges rather than boundaries in engagement. Based on our experiences with engagement in FEWS science and with Indigenous knowledges and languages, we consider examples of the role of language in reflecting worldviews, values, practices, and interactions in FEWS science and engagement. We particularly focus on Indigenous knowledges from Anishinaabe and the language of Anishinaabemowin, contrasting languages of boundaries and bridges through concrete examples. These examples are used to unpack the argument of this work, which is that scientific research aiming to engage FEWS issues in working landscapes requires grappling with embedded, practical understandings. This perspective demonstrates the importance of grappling with the role of language in creating boundaries or bridges, while recognizing that training in engagement may not critically reflect on the role of language in limiting diversity and inclusivity in engagement efforts. Leaving this reflexive consideration of language unexamined may unknowingly perpetuate boundaries rather than building bridges, thus limiting the effectiveness of engagement that is intended to address wicked problems in working landscapes.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Trade‐offs between reducing complex terminology and producing accurate interpretations from environmental DNA: Comment on “Environmental DNA: What's behind the term?” by Pawlowski et al., (2020) - Naiara Rodriguez‐Ezpeleta; Olivier Morissette; Colin W. Bean; Shivakumara Manu; Pritam Banerjee; Anaïs Lacoursière‐Roussel; Kingsly C. Beng; S. Elizabeth Alter; Fabian Roger; Luke E. Holman; Kathryn A. Stewart; Michael T. Monaghan; et al. (Molecular Ecology, 2021)
In a recent paper, “Environmental DNA: What's behind the term? Clarifying the terminology and recommendations for its future use in biomonitoring,” Pawlowski et al . argue that the term eDNA should be used to refer to the pool of DNA isolated from environmental samples, as opposed to only extra‐organismal DNA from macro‐organisms. We agree with this view. However, we are concerned that their proposed two‐level terminology specifying sampling environment and targeted taxa is overly simplistic and might hinder rather than improve clear communication about environmental DNA and its use in biomonitoring. This terminology is based on categories that are often difficult to assign and uninformative, and it overlooks a fundamental distinction within eDNA: the type of DNA (organismal or extra‐organismal) from which ecological interpretations are derived.

Phylogeographic analysis of foot‐and‐mouth disease virus serotype O dispersal and associated drivers in East Africa - Anna Munsey; Frank Norbert Mwiine; Sylvester Ochwo; Lauro Velazquez‐Salinas; Zaheer Ahmed; Francois Maree; Luis L. Rodriguez; Elizabeth Rieder; Andres Perez; Simon Dellicour; Kimberly VanderWaal (Molecular Ecology, 2021)
The continued endemicity of foot and mouth disease virus (FMDV) in East Africa has significant implications for livestock production and poverty reduction, yet its complex epidemiology in endemic settings remains poorly understood. Identifying FMDV dispersal routes and drivers of transmission is key to improved control strategies. Environmental heterogeneity and anthropogenic drivers (e.g., demand for animal products) can impact viral spread by influencing host movements. Here, we utilized FMDV serotype O VP1 genetic sequences and corresponding spatiotemporal data in order to (i) infer the recent dispersal history, and (II) investigate the impact of external factors (cattle density, human population density, proximity to livestock markets, and drought) on dispersal velocity, location, and direction of FMDV serotype O in East Africa. We identified statistical evidence of long‐distance transmission events, and we found that FMDV serotype O tends to remain circulating in areas of high cattle density, high human population density, and in close proximity to livestock markets. The latter two findings highlight the influence of anthropogenic factors on FMDV serotype O spread in this region. These findings contribute to the understanding of FMDV epidemiology in East Africa and can help guide improved control measures.

Silver nanoparticles against acute hepatopancreatic necrosis disease (AHPND) in shrimp and their depuration kinetics - Maribel Maldonado-Muñiz; Carlos Luna; Raquel Mendoza-Reséndez; Enrique Díaz Barriga-Castro; Sonia Soto-Rodriguez; Denis Ricque-Marie; Lucia Elizabeth Cruz-Suarez (Journal of Applied Phycology, 2020)

The impact of DNA demethylation on the upregulation of the NRN1 and TNFAIP3 genes associated with advanced gastric cancer - Fernanda Wisnieski; Leonardo Caires Santos; Danielle Queiroz Calcagno; Jaqueline Cruz Geraldis; Carolina Oliveira Gigek; Ana Carolina Anauate; Elizabeth Suchi Chen; Lucas Trevizani Rasmussen; Spencer Luiz Marques Payão; Ricardo Artigiani; Samia Demachki; Paulo Pimentel Assumpção; et al. (Journal of Molecular Medicine, 2020)

Quantifying species recovery and conservation success to develop an IUCN Green List of Species - H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Molly K. Grace; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; David A. Keith; Barney Long; David P. Mallon; Erik Meijaard; et al. (Conservation Biology, 2018)
Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action.

Permanent Cerebellar Degeneration After Acute Hyperthermia with Non-toxic Lithium Levels: a Case Report and Review of Literature - Fabian H. Rossi; Elisa Marie Rossi; Michael Hoffmann; Welwin Liu; Ramon Rodriguez Cruz; Natasha Antonovich; Arash Rezaei; Elizabeth Gonzalez; Maria Clara Franco; Alvaro Estevez; Florian Thomas (The Cerebellum, 2017)

Genetic diversity patterns in ex situ collections of Oryza officinalis Wall. ex G. Watt revealed by morphological and microsatellite markers - Maria Elizabeth Boncodin Naredo; Sheila Mae Quilloy Mercado; Maria Celeste Naynes Banaticla-Hilario; Myrricar Loren Berdos; Mario Alcantara Rodriguez; Kenneth Lee McNally; Ruaraidh Sackville Hamilton (Genetic Resources and Crop Evolution, 2017)

Metal enrichment of soils following the April 2012–2013 eruptive activity of the Popocatépetl volcano, Puebla, Mexico - P. F. Rodriguez-Espinosa; M. P. Jonathan; S. S. Morales-García; Lorena Elizabeth Campos Villegas; E. Martínez-Tavera; N. P. Muñoz-Sevilla; Miguel Alvarado Cardona (Environmental Monitoring and Assessment, 2015)

The effect of chronic phenytoin administration on single prolonged stress induced extinction retention deficits and glucocorticoid upregulation in the rat medial prefrontal cortex - Sophie A. George; Mariana Rodriguez-Santiago; John Riley; Elizabeth Rodriguez; Israel Liberzon (Psychopharmacology, 2015)

Population dynamics of Sonoran Desert saguaro cactus ( Carnegiea gigantea ) at the Desert Laboratory (Tucson, Arizona) - Susana Rodriguez-Buritica; Helen Raichle; Trevor Birt; Robert H. Webb; Raymond M. Turner; Elizabeth A. Pierson; D. Lawrence Venable (Ecology, 2013)
The saguaro cactus ( Carnegiea gigantea ) is one of the most iconic perennials in the Sonoran Desert. The ecological importance of this species has motivated studies that explored its physiological adaptations to deserts, factors controlling its recruitment and distribution, and changes in its population density and extent over time. The population of saguaros on Tumamoc Hill (Tucson, Arizona) is one of the best studied. Saguaros on and nearby Tumamoc Hill were mapped in 1908, and in 1964 R. M. Turner and J. R. Hastings established four 250‐m wide plots within the original census area. Plots were established on the north‐, south‐, east‐, and west‐facing slopes of Tumamoc Hill, and each plot extends from the top to the base of the hill. Plots were resurveyed in 1970, 1987, 1993, and between 2010 and 2012. In this Data Paper, we present all information associated with this monitoring program, which includes digital versions of Spalding's original 1908 saguaro map as well as information regarding individual saguaros located in each of the four plots. Collected data include plant height, number of branches, and plant condition, as well as plant location. Starting in 1993, we also noted the identity and condition of plant species growing in close proximity to each saguaro. The archived data set described here contains information pertaining to >5800 saguaros. Past analyses of these data include reconstructions of regeneration patterns from observed age structures and the determination of the average height‐specific growth rates for plants on each slope. The findings from these studies have broadened our understanding of the relationship between saguaro regeneration patterns and climate. These data have also provided pivotal information regarding regional trends of saguaro populations throughout the Sonoran Desert. As a group, the Tumamoc Hill censuses constitute one of the longest spatially explicit monitoring efforts for a single species in the world. They provide an observational baseline for future comparisons relating individual growth and population demographics to rising CO 2 levels, climate change, vegetation change, or changes in other biotic or abiotic factors.

Multifunctional Tumor-Targeted Polymer-Peptide-Drug Delivery System for Treatment of Primary and Metastatic Cancers - Pooja Chandna; Jayant J. Khandare; Elizabeth Ber; Lorna Rodriguez-Rodriguez; Tamara Minko (Pharmaceutical Research, 2010)

Family history of various cancers and pancreatic cancer mortality in a large cohort - Eric J. Jacobs; Carmen Rodriguez; Christina C. Newton; Elizabeth B. Bain; Alpa V. Patel; Heather Spencer Feigelson; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2009)

Metagenomic analysis of stressed coral holobionts - Rebecca Vega Thurber; Dana Willner‐Hall; Beltran Rodriguez‐Mueller; Christelle Desnues; Robert A. Edwards; Florent Angly; Elizabeth Dinsdale; Linda Kelly; Forest Rohwer (Environmental Microbiology, 2009)
Summary The coral holobiont is the community of metazoans, protists and microbes associated with scleractinian corals. Disruptions in these associations have been correlated with coral disease, but little is known about the series of events involved in the shift from mutualism to pathogenesis. To evaluate structural and functional changes in coral microbial communities, Porites compressa was exposed to four stressors: increased temperature, elevated nutrients, dissolved organic carbon loading and reduced pH. Microbial metagenomic samples were collected and pyrosequenced. Functional gene analysis demonstrated that stressors increased the abundance of microbial genes involved in virulence, stress resistance, sulfur and nitrogen metabolism, motility and chemotaxis, fatty acid and lipid utilization, and secondary metabolism. Relative changes in taxonomy also demonstrated that coral‐associated microbiota ( Archaea , Bacteria , protists) shifted from a healthy‐associated coral community (e.g. Cyanobacteria , Proteobacteria and the zooxanthellae Symbiodinium ) to a community (e.g. Bacteriodetes , Fusobacteria and Fungi ) of microbes often found on diseased corals. Additionally, low‐abundance Vibrio spp. were found to significantly alter microbiome metabolism, suggesting that the contribution of a just a few members of a community can profoundly shift the health status of the coral holobiont.

Use of blood-pressure-lowering medication and risk of prostate cancer in the Cancer Prevention Study II Nutrition Cohort - Carmen Rodriguez; Eric J. Jacobs; Anusila Deka; Alpa V. Patel; Elizabeth B. Bain; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2009)

Acute Disturbance of Lake Pontchartrain Benthic Communities by Hurricane Katrina - Michael A. Poirrier; Zoe Rodriguez del Rey; Elizabeth A. Spalding (Estuaries and Coasts, 2008)

Transcripts of MYB-like genes respond to phosphorous and nitrogen deprivation in Arabidopsis - Christopher D. Todd; Peiyu Zeng; Alicia M. Rodriguez Huete; Mary Elizabeth Hoyos; Joe C. Polacco (Planta, 2004)